2009
DOI: 10.1038/ni.1728
|View full text |Cite
|
Sign up to set email alerts
|

Antigen processing influences HIV-specific cytotoxic T lymphocyte immunodominance

Abstract: Although cytotoxic T lymphocytes (CTLs) in people infected with human immunodeficiency virus type 1 can potentially target multiple virus epitopes, the same few are recognized repeatedly. We show here that CTL immunodominance in regions of the human immunodeficiency virus type 1 group-associated antigen proteins p17 and p24 correlated with epitope abundance, which was strongly influenced by proteasomal digestion profiles, affinity for the transporter protein TAP, and trimming mediated by the endoplasmatic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
184
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(201 citation statements)
references
References 49 publications
13
184
0
4
Order By: Relevance
“…In addition, there have been isolated reports of peptides with residues overhanging the C-terminal pocket of HLA-A*02:01 12,40 and H2-M3 41 . It was not clear, however, whether such overhangs could occur beyond the more buried N-terminal pocket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there have been isolated reports of peptides with residues overhanging the C-terminal pocket of HLA-A*02:01 12,40 and H2-M3 41 . It was not clear, however, whether such overhangs could occur beyond the more buried N-terminal pocket.…”
Section: Discussionmentioning
confidence: 99%
“…The T-cell receptor (TCR) binds these bulged regions of the peptide whilst simultaneously contacting the HLA-I molecule. Isolated reports have described peptides that protrude at the C-terminus from the peptide-binding groove with the P-1 residue acting as an alternate C-terminal anchor, although the extent to which this represents a common occurrence remains unclear 11,12 . Such non-canonical HLA-I-peptide landscapes are important because they potentially form unique contact surfaces for TCR and killer immunoglobulin-like receptor (KIR) recognition with attendant implications for disease-relevant immune responses 12,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results obtained in the present study suggest the following two possibilities: First, FV9 and FP10/FV11 peptides were presented on the surface of HIV-1-infected cells dominantly and subdominantly, respectively. A previous study showed that CD8 + T-cell response hierarchies to overlapping epitope peptides correlated with the predicted epitope abundance on the cell surface [19]. Therefore, although antigen-processing profiles were not analyzed in the present study, the FV9 peptide would be predominantly presented by HLA-B*54:01 in HIV-1-infected cells.…”
Section: Discussionmentioning
confidence: 82%
“…2012. 42: 2621-2631 Immunity to infection 2629 peptide (residues 263-270: KRWIILGL) more efficiently than it does the KK10 one [19], suggesting that KL8 as well as KK10 peptide might be presented by HLA-B27 for recognition by CD8 + T cells though the former is much effectively presented by the latter. In addition, two distinct HLA-B57-restricted p24 Gag-derived peptides, KI8 (residues 162-169: KAFSPEVI) and KF11 (residues 162-172: KAFSPEVIPMF), were reported to be recognized by distinct CD8 + T-cell clones from an HLA-B57 + HIV-1-infected individual [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation